Immune mechanisms in human and canine demodicosis: A review. (8th October 2019) - Gazi, Umut; Taylan‐Ozkan, Aysegul; Mumcuoglu, Kosta Y.
Abstract: Demodex mites are saprophytic parasites of the mammalian skin, mostly found in or near pilosebaceous units of hairy regions. While they can be found in healthy humans and animals without causing any clinical manifestations, they were suggested to create pathogenic symptoms when they appear in high densities under favourable conditions (ie, demodicosis). Nevertheless, their role as the primary causative agent of the pathogenic conditions in humans is debated today. Canine demodicosis, which is highly prevalent in certain dog breeds, provides a valuable tool for studying the pathogenesis of human demodicosis. Canine and human demodicosis are caused by different Demodex species, and the clinical manifestations in former could be life‐threatening. Nevertheless, current literature suggests similar immune responses and immune evasion mechanisms in human and canine demodicosis; cellular immunity appeared to have a central role in protection against demodicosis, and Demodex mites were shown to influence both innate and adaptive immune response to escape immune attack. The aim of this review is to summarize the relevant literature on demodicosis obtained from studies conducted on both organisms, and draw the attention to the effect of mite‐associated factors (eg, microbiota) on the different clinical manifestations displayed during human and canine demodicosis.